Magnesium alloy material for spaceflight liquid ammonia heat pipe and preparation method of magnesium alloy material

By adding Al and rare earth elements to the magnesium alloy to form a spontaneous magnesium nitride protective film, the problem of poor corrosion resistance of magnesium alloy heat pipes in liquid ammonia environments is solved, and its service life and corrosion resistance are significantly improved.

CN119843126AActive Publication Date: 2025-04-18SHANGHAI JIAOTONG UNIV
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202510329585.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-20
Publication Date
2025-04-18
Estimated Expiration
2045-03-20

AI Technical Summary

Technical Problem

Magnesium alloy heat pipes have poor corrosion resistance in liquid ammonia environments. The prior art is difficult to significantly improve their liquid ammonia corrosion resistance without affecting the processing process of heat pipes.

Method used

By adding Al and rare earth elements such as Y, Nd, and Gd to the magnesium alloy, a magnesium alloy with a specific component ratio is formed, so that a layer of magnesium nitride protective film is spontaneously formed in the liquid ammonia environment to prevent liquid ammonia corrosion.

Benefits of technology

It significantly improves the service life of magnesium alloy in extreme environments, enhances corrosion resistance, and ensures good processing performance. It is suitable for manufacturing complex aerospace liquid ammonia heat pipe parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843126A_ABST
    Figure CN119843126A_ABST
Patent Text Reader

Abstract

The invention discloses a magnesium alloy material for a spaceflight liquid ammonia heat pipe and a preparation method of the magnesium alloy material, and belongs to the technical field of alloy materials. The magnesium alloy material comprises, by mass, 6%-11% of Al, 0.1%-1% of Mn, 0.1%-0.5% of Zn, 0.05%-0.5% of Y, 0.1%-3.0% of Nd, 0.1%-2.0% of Gd and the balance Mg and inevitable impurities. By adding Al and rare earth elements such as Y, Nd and Gd, the magnesium alloy with the specific component proportion can spontaneously form a layer of magnesium nitride protective film in a liquid ammonia environment, the protective film can effectively prevent liquid ammonia from corroding a magnesium alloy matrix, and the service life of the material in an extreme environment is remarkably prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of alloy materials, and in particular relates to a magnesium alloy material for aerospace liquid ammonia heat pipes and a preparation method thereof. Background Art

[0002] With the large-scale development of high-power spacecraft such as Internet satellites and civilian mobile electronic devices, the use of heat pipes in thermal management systems has increased dramatically. Heat pipes are efficient heat conduction devices, and their performance depends not only on the design of the internal structure, but also on the materials used. Heat pipes are divided into copper alloy heat pipes, aluminum alloy heat pipes, stainless steel heat pipes, magnesium alloy heat pipes and other material heat pipes according to different materials. Among them, the copper in copper alloy heat pipes has a high thermal conductivity, which makes copper alloy heat pipes very suitable for applications that require rapid heat transfer. In addition, copper has good corrosion resistance and can maintain a long service life in many environments; copper alloy heat pipes are often used in electronic equipment heat dissipation, precision instrument cooling and other fields. The aluminum density in aluminum alloy heat pipes is lower than that of copper, which means that aluminum alloy heat pipes are lighter than copper heat pipes. Although the thermal conductivity of aluminum is slightly lower than that of copper, it is still efficient enough and the cost is relatively low. Aluminum alloy heat pipes are widely used in portable electronic devices such as laptops and smart phones. The stainless steel material in stainless steel heat pipes has excellent corrosion resistance and can be used in harsh environments without being easily damaged. It is suitable for use in highly corrosive environments such as chemical industry and marine engineering. The magnesium in magnesium alloy heat pipes is the lightest of all commonly used metals, which makes magnesium alloy heat pipes an ideal choice for the pursuit of extreme lightweight design. However, magnesium alloys are prone to corrosion under certain environmental conditions, so special surface treatment or alloy formulation is required to enhance their durability. Magnesium alloy heat pipes are mainly used in aerospace, high-end electronic equipment and other application scenarios that require strict weight control.

[0003] In order to solve the problem of poor corrosion resistance of magnesium alloy heat pipes, the main methods include surface treatment, design of composite materials, nanotechnology, etc., or starting from the materials added to the heat pipe, using non-corrosive organic liquids instead of liquid ammonia. Among them, surface treatment mainly uses methods such as anodic oxidation or chemical conversion coating to form a protective film on the surface of magnesium alloy, thereby improving its corrosion resistance, but this makes the preparation method of magnesium alloy more complicated, and the original coating will be destroyed during the subsequent welding process of the heat pipe, reducing the service life of the heat pipe. Designing composite materials mainly combines magnesium alloy with other materials (such as carbon fiber) to make composite materials, so as to make use of their respective advantages and make up for their respective shortcomings. However, in composite materials, the interface strength between the matrix and the reinforcement phase directly affects the overall performance of the material, and poor interface may lead to a decrease in material performance. Using nanotechnology to modify magnesium-based materials can not only improve their strength and toughness, but also improve their thermal conductivity and corrosion resistance. However, the synthesis of nanomaterials usually requires the use of special equipment and techniques, such as chemical vapor deposition (CVD), atomic layer deposition (ALD), etc. These technologies are expensive and face challenges in large-scale production. In addition, nanoparticles prepared by nanotechnology are prone to agglomeration, which will cause the material performance to fall short of the expected level. The internal working medium is replaced with organic liquids such as ethanol and acetone that do not corrode metals, but the thermal conductivity of this type of heat pipe is not as high as that using liquid ammonia as the working medium.

[0004] In order to solve the problem of poor corrosion resistance of magnesium alloy heat pipes, another method is alloying, which changes the basic composition of magnesium alloys by adding other elements to enhance their physical and chemical properties. Through alloying, the plasticity, toughness and other properties of the material can be adjusted, making the material easier to process and form, and the preparation method is simple and easy to operate. However, not all elements are compatible with each other during the alloying process. There may be complex interactions between elements, and chemical reactions may occur between certain elements, resulting in unstable alloy performance or even failure.

[0005] Therefore, there is an urgent need for a method to improve the liquid ammonia corrosion resistance of magnesium alloys through alloying. Summary of the invention

[0006] The purpose of the present invention is to provide a magnesium alloy material for aerospace liquid ammonia heat pipes and a preparation method thereof, so as to solve the problem that the design process of the magnesium alloy elements is relatively complicated and the magnesium alloy has poor liquid ammonia corrosion resistance. The present invention adds Al and rare earth elements such as Y, Nd, and Gd, and the magnesium alloy with a specific composition ratio can spontaneously form a magnesium nitride protective film in a liquid ammonia environment. This protective film can effectively prevent the corrosion of liquid ammonia on the magnesium alloy matrix, significantly improving the service life of the material in extreme environments.

[0007] To achieve the above-mentioned purpose, the first aspect of the present invention provides a magnesium alloy material for aerospace liquid ammonia heat pipes, wherein the magnesium alloy material comprises, by mass percentage, Al 6%~11%, Mn 0.1%~1%, Zn 0.1%~0.5%, Y 0.05%~0.5%, Nd0.1%~3, Gd 0.1%~2.0% and the remainder Mg and unavoidable impurities.

[0008] Preferably, the crystal structure of the magnesium alloy material is a close-packed hexagonal crystal structure.

[0009] Magnesium alloy materials can be used to prepare magnesium alloy heat pipes for aerospace use. Their density is 1 / 3 lower than that of traditional aluminum alloy liquid ammonia heat pipes, which can achieve lightweight aerospace components. However, magnesium alloy heat pipes need to be filled with liquid ammonia, and magnesium alloys have low corrosion resistance to liquid ammonia. In response to this problem, in the prior art, an anti-corrosion coating is generally provided on the surface of the magnesium alloy heat pipe to increase the service life of the magnesium alloy heat pipe. However, this method will destroy the original anti-corrosion coating during the subsequent processing of the heat pipe, and the preparation process of the anti-corrosion coating is also relatively complicated. Therefore, it is necessary to study a material that can improve the corrosion resistance of magnesium alloy to liquid ammonia without replacing the liquid ammonia in the heat pipe. The present invention is designed for the material composition of magnesium alloys. By adding Al and rare earth elements such as Y, Nd, and Gd, the addition of this specific component enables the magnesium alloy to spontaneously form a layer of magnesium nitride protective film in a liquid ammonia environment. This protective film can effectively prevent the corrosion of liquid ammonia on the magnesium alloy matrix, significantly improving the service life of the material in extreme environments.

[0010] The present invention has specific restrictions on the amount of each element added. Once the amount is exceeded, the liquid ammonia corrosion resistance of the magnesium alloy material will be adversely affected. Among them, aluminum is one of the most commonly used reinforcing elements of magnesium alloy materials. If the amount of aluminum added is too high, it will not only increase the cost of the material, but also form a brittle phase, resulting in a decrease in the plasticity of the material, affecting the ductility and corrosion resistance of the material. Manganese can improve the thermal stability and corrosion resistance of magnesium alloy materials, but if the manganese content is too high, the liquid ammonia corrosion resistance of magnesium alloy materials will be reduced. Zinc can improve the strength of magnesium alloys, but too much zinc will cause the plasticity of the alloy to decrease, thereby reducing its processing performance; in addition, the volatilization of zinc at high temperatures may also affect the stability and uniformity of the alloy. Rare earth elements such as Y (yttrium), Nd (neodymium) and Gd (gadolinium) can improve the mechanical properties and thermal stability of magnesium alloys, but if the content is too high, too many reinforcing phases may be formed, causing the material to become brittle, and the cost of rare earth elements is high, and excessive use will increase the material cost.

[0011] A second aspect of the present invention provides a method for preparing a magnesium alloy material for aerospace liquid ammonia heat pipes, comprising the following steps: (1) According to the mass percentage of magnesium alloy materials, weigh pure magnesium, pure aluminum, magnesium-aluminum alloy, magnesium-manganese alloy, manganese chloride, aluminum-manganese alloy, pure zinc, magnesium-zinc alloy, magnesium-yttrium master alloy, magnesium-neodymium master alloy, and magnesium-gadolinium master alloy; (2) Smelting pure magnesium, and after the pure magnesium is melted, adding pure aluminum, magnesium-aluminum alloy, magnesium-manganese alloy, manganese chloride, aluminum-manganese alloy, pure zinc, magnesium-zinc alloy, magnesium-yttrium master alloy, magnesium-neodymium master alloy, and magnesium-gadolinium master alloy, and continuing to smelt until all the materials are melted to obtain a melt; (3) refining the molten metal and then casting it to obtain an ingot; (4) The ingot is heat treated and cooled to room temperature to obtain a magnesium alloy material.

[0012] Preferably, the melting temperature of pure magnesium is 650°C.

[0013] Preferably, the temperature for continued smelting is 750°C.

[0014] Preferably, the casting method is one of gravity casting, high pressure casting, low pressure casting, differential pressure casting or semi-continuous casting.

[0015] Gravity casting is a casting method that uses the weight of the metal to pour molten metal into the mold. The specific process of gravity casting is: Under an argon protective atmosphere, the magnesium alloy melt (melt) is taken out from the melting crucible using a container coated with water glass coating, and the melt is poured into an ingot mold preheated at 200°C by gravity. The melt is then cooled and solidified to obtain a cast ingot.

[0016] High pressure casting, also known as high pressure die casting, is a casting method that uses high pressure to press molten metal into the mold cavity. The specific process of high pressure casting is: The magnesium alloy melt is transferred to the injection chamber of the die-casting machine. The melt temperature is maintained between 620 and 680°C, the injection pressure ratio is controlled at 40 to 70 MPa, and the mold temperature is maintained between 180 and 250°C. The casting is taken out after the die-casting is completed.

[0017] Low-pressure casting is a casting method in which a mold is placed above a sealed crucible, compressed inert gas is introduced into the crucible, low pressure is created on the surface of the molten metal, and the molten metal rises from the riser to fill the mold and control solidification. The specific process of low-pressure casting is as follows: Use a cover plate with a riser to cover and seal the melting crucible, place the mold directly above the riser and align it with the mold runner, cast at 680-720°C, introduce 0.02-0.05MPa of compressed inert gas into the closed crucible to lift the magnesium alloy melt in the crucible into the mold, then maintain the pressure at 0.05-0.08MPa for 120s, release the pressure after the melt in the mold solidifies, and remove the mold.

[0018] Differential pressure casting is an improved casting process of low-pressure casting. The difference is that the differential pressure casting is covered with a sealing cover outside the casting mold, which is filled with compressed gas, so that the casting mold is under a certain pressure of the gas. The specific process of differential pressure casting is: The process of differential pressure casting is basically the same as that of low pressure casting. The difference is that differential pressure casting requires the introduction of compressed gas into the sealing cover and the crucible at the same time, and the pressure inside the crucible is slightly higher than the pressure inside the sealing cover. The pressure difference is controlled between 0.03 and 0.06 MPa.

[0019] Semi-continuous casting is a casting method in which the molten metal is uniformly introduced into a crystallizer whose outer wall is cooled by water, and the molten metal is rapidly solidified and crystallized under the joint action of the crystallizer wall and the crystallizer base to finally form an ingot. The specific process of semi-continuous casting is as follows: The magnesium alloy melt is directly transported to the semi-continuous casting crystallizer. The crystallizer is made of copper alloy, with a height of 180~220mm, a water hole diameter of 2~3mm, a casting temperature of 700~720℃, a casting speed of 25~45mm / min, a cooling water temperature of 10~30℃, a cooling water pressure of 0.1~0.3MPa, and a cooling water intensity of 250~350L / min. Semi-continuous casting is carried out under the following conditions.

[0020] Preferably, the heat treatment includes at least one of solution heat treatment and aging heat treatment.

[0021] Preferably, the solution heat treatment method is to perform heat preservation treatment at 350-420° C. for 8-12 hours and quench with cold water.

[0022] Preferably, the aging heat treatment method is to carry out heat preservation treatment at 200-300°C for 24-48 hours and then cool down in the furnace.

[0023] Therefore, the present invention adopts the above-mentioned magnesium alloy material for aerospace liquid ammonia heat pipe and its preparation method, which has the following beneficial effects: 1. The present invention adds Al and rare earth elements such as Y, Nd, and Gd. This magnesium alloy with a specific composition ratio can spontaneously form a magnesium nitride protective film in a liquid ammonia environment. This protective film can effectively prevent the corrosion of liquid ammonia to the magnesium alloy matrix, and significantly improve the service life of the material in extreme environments.

[0024] 2. The magnesium alloy composition designed in the present invention not only enhances the corrosion resistance of the material, but also ensures good processing performance. The alloy can be processed and formed by conventional processes such as extrusion, and is suitable for manufacturing complex aerospace liquid ammonia heat pipe components.

[0025] 3. The present invention adopts a specific heat treatment process (such as solution treatment and / or aging treatment) to make the second phase particles inside the alloy evenly distributed, avoiding the risk of local corrosion caused by aggregation of second phase particles, and further improving the overall corrosion resistance and mechanical properties of the material.

[0026] 4. The magnesium alloy of the present invention has a relatively low density, combined with excellent mechanical properties, so that the heat pipe made of this material is both light and strong, and is very suitable for use in spacecraft with strict weight restrictions.

[0027] 5. Compared with other high-performance alloys, the magnesium alloy of the present invention has better cost-effectiveness and generates relatively less environmental pollution during the production process; in addition, magnesium is a renewable resource, which makes magnesium alloy a sustainable development option and meets the current demand for green and environmentally friendly materials.

[0028] The technical solution of the present invention is further described in detail below through embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is the liquid ammonia corrosion test structure diagram; Figure 2 It is a liquid ammonia corrosion test device at room temperature; Figure 3 It is a liquid ammonia corrosion test device at 80℃; Figure 4 This is a SEM image of the magnesium alloy material prepared in Example 1 after corrosion for 3 months; Figure 5 This is an EDS image of the magnesium alloy material prepared in Example 1 after corrosion for 3 months; Figure 6 This is the SEM image of conventional AZ31B magnesium alloy after corrosion for 3 months. DETAILED DESCRIPTION

[0030] The present invention will be further described below. It should be noted that this embodiment is based on the technical solution and provides a detailed implementation method and a specific operation process, but the present invention is not limited to this embodiment.

[0031] The compositions of the magnesium alloy materials of Examples 1 to 5 are shown in Table 1.

[0032] Table 1 Magnesium alloy material composition of Examples 1 to 5

[0033] The method for preparing a magnesium alloy material for aerospace liquid ammonia heat pipe in the above embodiment comprises the following steps: (1) According to the mass percentage of magnesium alloy materials, weigh pure magnesium, pure aluminum, magnesium-aluminum alloy, magnesium-manganese alloy, manganese chloride, aluminum-manganese alloy, pure zinc, magnesium-zinc alloy, magnesium-yttrium master alloy, magnesium-neodymium master alloy, and magnesium-gadolinium master alloy; (2) Smelting pure magnesium, and after the pure magnesium is melted, adding pure aluminum, magnesium-aluminum alloy, magnesium-manganese alloy, manganese chloride, aluminum-manganese alloy, pure zinc, magnesium-zinc alloy, magnesium-yttrium master alloy, magnesium-neodymium master alloy, and magnesium-gadolinium master alloy, and continuing to smelt until all the materials are melted to obtain a melt; (3) refining the molten metal and then casting it to obtain an ingot; The casting method is gravity casting, and the specific process is: Under an argon protective atmosphere, a magnesium alloy melt (molten liquid) is taken out from a melting crucible using a container coated with a water glass coating, and the melt is poured into an ingot mold preheated at 200°C by gravity, and then the melt is cooled and solidified to obtain a cast ingot; (4) heat treating the ingot and cooling it to room temperature to obtain a magnesium alloy material; The heat treatment is solution heat treatment, and the solution heat treatment method is to keep the temperature at 400°C for 10 hours and quench with cold water.

[0034] Comparative Example 1 The difference between this comparative example and Example 1 is that the amount of Al added is increased. The specific magnesium alloy material composition and content are as follows: The magnesium alloy material includes, by mass percentage, Al 15%, Mn 0.3%, Zn 0.3%, Y 0.08%, Nd 2.5%, Gd 0.5%, and the balance Mg and inevitable impurities.

[0035] Comparative Example 2 The difference between this comparative example and Example 1 is that the amount of Mn added is increased. The specific composition and content of the magnesium alloy material are as follows: The magnesium alloy material includes, by mass percentage, 7% Al, 2% Mn, 0.3% Zn, 0.08% Y, 2.5% Nd, 0.5% Gd, and the balance Mg and inevitable impurities.

[0036] Comparative Example 3 The difference between this comparative example and Example 1 is that the amount of Zn added is increased. The specific magnesium alloy material composition and content are as follows: The magnesium alloy material includes, by mass percentage, 7% Al, 0.3% Mn, 1% Zn, 0.08% Y, 2.5% Nd, 0.5% Gd, and the balance Mg and inevitable impurities.

[0037] Comparative Example 4 The difference between this comparative example and Example 1 is that the amount of Y added is increased. The specific magnesium alloy material composition and content are as follows: The magnesium alloy material includes, by mass percentage, 7% Al, 0.3% Mn, 0.3% Zn, 1% Y, 2.5% Nd, 0.5% Gd, and the balance Mg and inevitable impurities.

[0038] Comparative Example 5 The difference between this comparative example and Example 1 is that the amount of Nd added is increased. The specific magnesium alloy material composition and content are as follows: The magnesium alloy material includes, by mass percentage, 7% Al, 0.3% Mn, 0.3% Zn, 0.08% Y, 4% Nd, 0.5% Gd, and the balance Mg and inevitable impurities.

[0039] Comparative Example 6 The difference between this comparative example and Example 1 is that the amount of Gd added is increased. The specific composition and content of the magnesium alloy material are as follows: The magnesium alloy material includes, by mass percentage, 7% Al, 0.3% Mn, 0.3% Zn, 0.08% Y, 2.5% Nd, 5% Gd, and the balance Mg and inevitable impurities.

[0040] Comparative Example 7 The difference between this comparative example and Example 1 is that no Y element is added. The specific magnesium alloy material composition and content are as follows: The magnesium alloy material includes, by mass percentage, 7% Al, 0.3% Mn, 0.3% Zn, 2.5% Nd, 0.5% Gd, and the balance Mg and inevitable impurities.

[0041] Comparative Example 8 The difference between this comparative example and Example 1 is that no Nd element is added. The specific magnesium alloy material composition and content are as follows: The magnesium alloy material includes, by mass percentage, 7% Al, 0.3% Mn, 0.3% Zn, 0.08% Y, 0.5% Gd, and the balance Mg and inevitable impurities.

[0042] Comparative Example 9 The difference between this comparative example and Example 1 is that no Gd element is added. The specific magnesium alloy material composition and content are as follows: The magnesium alloy material includes, by mass percentage, 7% Al, 0.3% Mn, 0.3% Zn, 0.08% Y, 2.5% Nd, and the balance Mg and inevitable impurities.

[0043] Comparative Example 10 The difference between this comparative example and Example 1 is that the magnesium alloy material is conventional AZ31B magnesium alloy.

[0044] The composition of AZ31B magnesium alloy is Al: 2.5~3.5%, Zn: 0.6~1.4%, Mn: 0.2~1%, and Mg balance and trace impurities in mass percentage.

[0045] Performance Testing (1) Since liquid ammonia is very easy to vaporize and its vapor pressure is as high as 20 atmospheres, liquid ammonia corrosion must be carried out in a sealed pressure vessel. The magnesium alloy prepared in the embodiment and the comparative example was processed into a round rod with a diameter of 5 mm and a length of 35 mm, and placed in a stainless steel gravity heat pipe filled with liquid ammonia. The temperatures of the upper, middle and lower measuring points of the gravity heat pipe were measured at room temperature and an 80°C oil bath, respectively. If the magnesium alloy corrodes in liquid ammonia, hydrogen will be generated and accumulated in the upper part of the gravity heat pipe, resulting in a measurable temperature difference between the upper and lower temperature measuring points; if no corrosion reaction occurs, the temperature difference between the upper, middle and lower temperature measuring points is small (within 0.5 degrees Celsius). The structure of the temperature measuring points, gravity heat pipe, heating plate and magnesium alloy sample is shown in Figure 1 .

[0046] (2) The magnesium alloy material prepared in Example 1 was subjected to corrosion tests at room temperature and 80°C oil bath conditions. The test results are shown in Table 2-3. Three parallel samples were tested at each temperature and the average value was taken.

[0047] Test at room temperature: After three months of testing at room temperature (November 2023 to February 2024), the temperature records of the upper, middle and lower three temperature measurement points of the gravity heat pipe equipped with the magnesium alloy are shown in Table 2 below. It can be seen from Table 2 that the temperature difference between the upper and lower measurement points is less than 0.5 degrees Celsius, and the magnesium alloy on the surface has not been corroded by liquid ammonia. Room temperature test device see Figure 2 .

[0048] Table 2 Liquid ammonia corrosion resistance test results of magnesium alloy materials prepared in Example 1 at room temperature

[0049] Tested at 80℃: The part of the gravity heat pipe containing magnesium alloy was placed in an oil bath at 80 degrees Celsius for heating to evaluate the corrosion resistance of the magnesium alloy in liquid ammonia after heating. The test results are shown in Table 3. Figure 3 shown.

[0050] Table 3 Liquid ammonia corrosion resistance test results of the magnesium alloy material prepared in Example 1 at 80°C

[0051] (3) The surface morphology of the magnesium alloy material of Example 1 after being corroded in heated liquid ammonia for three months was tested by SEM. Figure 4 It can be seen that the surface of the magnesium alloy is still relatively smooth, and the knife marks left by the machining surface are still clearly visible, and no corrosion products are found to cover it. This shows that the magnesium alloy material prepared by the present invention has excellent liquid ammonia corrosion resistance. The surface layer composition was analyzed using an energy dispersive spectrometer (EDS), and the results are as follows: Figure 5 As shown in Table 4, the main component is magnesium oxide (MgO) because magnesium nitride quickly changes into magnesium oxide (MgO) after contacting moisture in the air.

[0052] Table 4 Analysis results of element content in the surface layer

[0053] (4) A gravity heat pipe containing conventional AZ31B magnesium alloy (Comparative Example 10) and a gravity heat pipe without any magnesium alloy sample was tested for one month in a high temperature environment of 80 degrees Celsius, and the temperatures of the upper, middle and lower temperature points were measured. The results are shown in Table 5. As can be seen from Table 5, the conventional magnesium alloy produces excessive hydrogen due to the reaction with liquid ammonia, which accumulates at the top of the gravity heat pipe, resulting in the heat pipe being unable to effectively transfer heat through ammonia, and a significant temperature difference between the upper and lower temperature measurement points. The corroded AZ31B magnesium alloy was taken out and characterized by SEM, as shown below Figure 6 As shown in the figure, it can be seen that the surface is covered by corrosion products, indicating that AZ31B magnesium alloy is not resistant to liquid ammonia corrosion.

[0054] Table 5 Liquid ammonia corrosion resistance test results of conventional AZ31B magnesium alloy of comparative example 7 at 80°C

[0055] (5) The magnesium alloy materials prepared in the examples and comparative examples were processed into round rods with a diameter of 5 mm and a length of 35 mm, and placed in a stainless steel gravity heat pipe filled with liquid ammonia. The temperatures of the upper, middle and lower measuring points of the gravity heat pipe were measured at room temperature, and the temperature difference between the lower measuring point and the upper measuring point was calculated. The test results are shown in Table 6.

[0056] Table 6 Liquid ammonia corrosion resistance test results

[0057] It can be seen from the above performance test results that Examples 1-5 have good liquid ammonia corrosion resistance, especially Example 1 has the most outstanding comprehensive performance. This is mainly because the present invention adds Al and rare earth elements such as Y, Nd, and Gd to the magnesium alloy material. The magnesium alloy with this specific composition ratio can spontaneously form a magnesium nitride protective film in a liquid ammonia environment. This protective film can effectively prevent the corrosion of liquid ammonia on the magnesium alloy substrate.

[0058] However, the comparative examples are obviously inferior to the embodiments in the corresponding performance tests because they do not adopt the necessary technical solutions. In comparative example 1, the content of aluminum element is changed, and the content of aluminum element exceeds the range specified by the present invention. From the results, it can be seen that the temperature difference between the upper temperature measuring point and the lower temperature measuring point becomes larger, and the liquid ammonia corrosion resistance of the magnesium alloy material decreases, which proves that the addition of aluminum element has an important influence on the corrosion resistance of the magnesium alloy material. Comparative examples 2-6 increase the content of manganese element, zinc element, yttrium element, neodymium element and gadolinium element respectively, which exceeds the range specified by the present invention. From the results, it can be seen that the temperature difference between the upper temperature measuring point and the lower temperature measuring point increases to varying degrees compared with embodiments 1-5, which proves that the addition of manganese element, zinc element, yttrium element, neodymium element and gadolinium element has a very important influence on the corrosion resistance of the magnesium alloy material. Comparative Examples 7-9 do not add the rare earth elements yttrium, neodymium, and gadolinium. From the results, it can be seen that the temperature difference between the upper temperature measuring point and the lower temperature measuring point is further increased, indicating that the addition of the three rare earth elements in the present invention is very important for improving the corrosion resistance of the magnesium alloy material, and it can also be proved that the simultaneous addition of the three rare earth elements has a synergistic effect. Comparative Example 10 uses a conventional AZ31B magnesium alloy, which contains Mg, Al, Zn, Mn, Si, Fe, Cu and Ni, and does not contain the three rare earth elements Y, Nd, and Gd in the present invention. From the results, it can be seen that the temperature difference between the upper temperature measuring point and the lower temperature measuring point is increased to 19.3°C, which indicates that the magnesium alloy is severely corroded, further proving the importance of adding the three rare earth elements Y, Nd, and Gd in the present invention. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.

[0059] Therefore, the present invention adopts a magnesium alloy material of the above structure for aerospace liquid ammonia heat pipes and a preparation method thereof. By adding Al and rare earth elements such as Y, Nd, and Gd, this magnesium alloy with a specific composition ratio can spontaneously form a magnesium nitride protective film in a liquid ammonia environment. This protective film can effectively prevent liquid ammonia from corroding the magnesium alloy matrix, significantly improving the service life of the material in extreme environments.

[0060] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A magnesium alloy material for aerospace liquid ammonia heat pipe, characterized in that: The magnesium alloy material includes, by mass percentage, Al 6%~11%, Mn 0.1%~1%, Zn 0.1%~0.5%, Y 0.05%~0.5%, Nd 0.1%~3%, Gd 0.1%~2.0% and the remainder Mg and inevitable impurities.

2. The magnesium alloy material for aerospace liquid ammonia heat pipe according to claim 1, characterized in that: The crystal structure of magnesium alloy materials is a close-packed hexagonal crystal structure.

3. The method for preparing a magnesium alloy material for aerospace liquid ammonia heat pipe according to any one of claims 1 to 2, characterized in that: The following steps are involved: (1) According to the mass percentage of magnesium alloy materials, weigh pure magnesium, pure aluminum, magnesium-aluminum alloy, magnesium-manganese alloy, manganese chloride, aluminum-manganese alloy, pure zinc, magnesium-zinc alloy, magnesium-yttrium master alloy, magnesium-neodymium master alloy, and magnesium-gadolinium master alloy; (2) Smelting pure magnesium, and after the pure magnesium is melted, adding pure aluminum, magnesium-aluminum alloy, magnesium-manganese alloy, manganese chloride, aluminum-manganese alloy, pure zinc, magnesium-zinc alloy, magnesium-yttrium master alloy, magnesium-neodymium master alloy, and magnesium-gadolinium master alloy, and continuing to smelt until all the materials are melted to obtain a melt; (3) refining the molten metal and then casting it to obtain an ingot; (4) The ingot is heat treated and cooled to room temperature to obtain a magnesium alloy material.

4. The method for preparing a magnesium alloy material for aerospace liquid ammonia heat pipe according to claim 3, characterized in that: The casting method is one of gravity casting, high pressure casting, low pressure casting, differential pressure casting or semi-continuous casting.

5. The method for preparing a magnesium alloy material for aerospace liquid ammonia heat pipe according to claim 3, characterized in that: The heat treatment includes at least one of solution heat treatment and aging heat treatment.

6. The method for preparing a magnesium alloy material for aerospace liquid ammonia heat pipe according to claim 5, characterized in that: The solution heat treatment method is to keep the temperature at 350~420℃ for 8~12h and quench with cold water.

7. The method for preparing a magnesium alloy material for aerospace liquid ammonia heat pipe according to claim 5, characterized in that: The aging heat treatment method is to keep the temperature at 200~300℃ for 24~48h and cool it with the furnace.

Citation Information

Patent Citations

  • Anti-corrosion Mg-Al-Zn-Mn cast magnesium alloy containing rare earth elementarysubstance Er

    CN101509092A

  • Magnesium alloy and preparation method thereof

    CN102534327A

  • Anti-corrosion wrought magnesium alloy containing rare earth elements and manufacturing method of anti-corrosion wrought magnesium alloy

    CN105624494A

  • High-strength fatigue-resistant rare earth magnesium alloy and preparation method thereof

    CN105821269A

  • Magnesium alloy as well as preparation method and application thereof

    CN107099713A